Effectiveness of Health Education on Postpartum Care on Accelerating Perineal Wound Healing - Ulfa, Siti Maria; Ghita, Dwi; Hasrida, Hasrida (Oshada, 2025)
Perineal wounds are a common form of maternal morbidity during the postpartum period and have the potential to cause serious complications if not managed appropriately. Although the postpartum phase is a critical period in maternal health recovery, attention to perineal wound care education remains suboptimal. This study aims to analyze the effectiveness of health education in accelerating perineal wound healing based on a recent literature review. The method used was a literature review with a descriptive qualitative approach, examining various research findings from 2020-2025. The synthesis of results shows that systematic and contextual educational interventions can improve mothers' knowledge, self-efficacy, and skills in independently caring for perineal wounds. The use of educational media such as booklets, videos, and digital applications has proven effective, especially when delivered with an empathetic approach by health workers such as midwives. Community-based interventions also expand the reach of education, especially in areas with limited access. These findings underscore the importance of integrating health education into postpartum care standards and the need for communication training for health workers. Overall, health education has proven to be a key strategy in reducing the rate of perineal wound complications and improving the quality of life of postpartum mothers through a sustainable promotive and preventive approach.